2022
DOI: 10.1101/2022.03.01.482445
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Balancing activation and costimulation of CAR tunes signaling dynamics and enhances therapeutic potency

Abstract: Background: Primary human T cells engineered with chimeric antigen receptors (CARs) ex vivo can be adoptively transferred to treat cancer. CD19-targeting CAR with CD28 costimulatory domain and CD3ζ activation domain have been approved by the US FDA for treating B cell malignancies. Methods: Here we generated mutation of immunorecpetor tyrosine-based activation motifs (ITAMs) in CD3ζ, namely 1XX CAR, which altered the balance of activation and costimulation. Next we investigated whether 1XX design could enhance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It has been postulated that increasing the number of ITAMs can lead to higher sensitivity and potency, thereby minimizing the required number of engaged receptors for an equivalent response [ 26 , 67 ]. However, in vivo studies demonstrated that CD19 CARs harboring a mutated CD3ζ signaling domain with only one functional ITAM located proximally to the membrane and ablation of the second and third ITAMs (1XX) outperformed the standard CARs containing a full CD3ζ chain, while inactivation of the two N-terminal ITAMs (XX3) demonstrated decreased efficiency [ 68 , 69 ]. Despite those advances regarding optimal ITAM positioning and number in the CD3ζ chain, the diverse roles of the other CD3 chains are currently extensively studied, not only in regard to the TCR but also as additional or alternative domains in the CAR [ 70 ].…”
Section: Part I—tcr Versus Carmentioning
confidence: 99%
“…It has been postulated that increasing the number of ITAMs can lead to higher sensitivity and potency, thereby minimizing the required number of engaged receptors for an equivalent response [ 26 , 67 ]. However, in vivo studies demonstrated that CD19 CARs harboring a mutated CD3ζ signaling domain with only one functional ITAM located proximally to the membrane and ablation of the second and third ITAMs (1XX) outperformed the standard CARs containing a full CD3ζ chain, while inactivation of the two N-terminal ITAMs (XX3) demonstrated decreased efficiency [ 68 , 69 ]. Despite those advances regarding optimal ITAM positioning and number in the CD3ζ chain, the diverse roles of the other CD3 chains are currently extensively studied, not only in regard to the TCR but also as additional or alternative domains in the CAR [ 70 ].…”
Section: Part I—tcr Versus Carmentioning
confidence: 99%